2020
DOI: 10.1155/2020/9715060
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory Activity of a Traditional Sri Lankan Concoction of Coriandrum sativum L. and Coscinium fenestratum G.

Abstract: Objective. To investigate the immunomodulatory activity of a traditional Sri Lankan concoction of Coriandrum sativum L. and Coscinium fenestratum (Gaertn.) Colebr., which is a Sri Lankan traditional medicine used to relieve inflammation and cold. Methods. In vivo anti-inflammatory activity was tested using carrageenan-induced rat paw-edema model. Mechanism of anti-inflammatory activity was assessed by investigating the production of nitric oxide (NO), expression of iNOS enzyme, and reactive oxygen species (ROS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 41 publications
1
11
0
Order By: Relevance
“…To give more proof to this finding is the unpublished finding of higher lymphocytes count for the LD group, but not for the HD group, compared with the count for the control. The present findings agree with the previous studies on healthy rats administered with methanolic leaf extract of Moringa oleifera, [33] and the concoction of Coriandrum sativum and Coscinium fenestratum [38], and on mice using an extract of zapoteca portoricensis [34] which showed a significantly higher mean haemagglutinating antibody titer to sheep red blood cells. The current results are in disagreement with a previous study [39] in healthy mice administered with the aqueous extract of Stachytarpetha jamaicensis, which resulted in significantly higher haemagglutinating antibody titer compared with the control group.…”
Section: Delayed Type Hypersensitivity Reactionsupporting
confidence: 93%
“…To give more proof to this finding is the unpublished finding of higher lymphocytes count for the LD group, but not for the HD group, compared with the count for the control. The present findings agree with the previous studies on healthy rats administered with methanolic leaf extract of Moringa oleifera, [33] and the concoction of Coriandrum sativum and Coscinium fenestratum [38], and on mice using an extract of zapoteca portoricensis [34] which showed a significantly higher mean haemagglutinating antibody titer to sheep red blood cells. The current results are in disagreement with a previous study [39] in healthy mice administered with the aqueous extract of Stachytarpetha jamaicensis, which resulted in significantly higher haemagglutinating antibody titer compared with the control group.…”
Section: Delayed Type Hypersensitivity Reactionsupporting
confidence: 93%
“…However, ELISAs to determine the specific IgM and IgG antibody concentrations raised against immunogens such as keyhole limpet hemocyanin (KLH) [22] or BSA [23] have became the preferred assays to measure the humoral immunity [ 24 ]. Our previous studies have also used the hemagglutination assay [ 9 ] or ELISA (unpublished data) for the detection of antibodies against SRBC to describe the immunostimulatory activity of the concoction of C. sativum and C. fenestratum . The present study deployed the use of ELISA to determine anti-BSA specific IgM and IgG responses to demonstrate the immunostumulatory activity of LS.…”
Section: Discussionmentioning
confidence: 99%
“…Different medicinal plants and combinations have been shown to exhibit immunostimulatory activity including several formulations and concoctions which contain some of the ingredients in LS. A recent study on a Sri Lankan traditional concoction consisting two ingredients found in LS, ie, Coriandrum sativum and Coscinium fenestratum had demonstrated its immunostimulatory activity [ 9 ]. Other studies have demonstrated the effect of different A yurvedic preparations/polyherbal formulations on immunomodulation/immunostimulation using animal models.…”
Section: Introductionmentioning
confidence: 99%
“…In vivo anti-inflammatory and immunostimulatory activity of Coriandrum sativu was studied using carrageenan-induced rat paw edema model which showed significant inhibition of nitric oxide, membrane stabilizing activity, superoxide production, and production of antibody [15] . Methanol extracts of Coriandrum sativum made from leaves and seeds were analyzed.…”
Section: Coriandrum Sativum Lmentioning
confidence: 99%